Thiamet-G facilitates reparative dentin formation via modulating O-GlcNAcylation and inflammation - Pokharel, Elina; Kim, Tae-Young; Rana, Bandana; Jang, Je-Hee; Lee, Jae-Hee; An, Seo-Young; An, Chang-Hyeon; Yamamoto, Hitoshi; Kim, Mee-Seon; Sohn, Wern-Joo; Lee, Youngkyun; Ha, Jung-Hong; et al. (Frontiers in Physiology, 2026)
IntroductionO-GlcNAcylation, a reversible post-translational modification regulated by O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA), is involved in various cellular processes, such as proliferation, differentiation, and inflammation modulation. Developmental study revealed that proper O-GlcNAcylation mediated by OGT is vital for tooth morphogenesis. However, the function of O-GlcNAcylation during reparative dentin formation is still unknown. To understand its therapeutic relevance in regenerative dentistry, we examined the potential of OGA inhibitor, Thiamet-G, in reparative dentin formation using both in vitro and in vivo approaches.MethodsHuman dental pulp stem cells were cultivated to examine cell viability, alkaline phosphatase (ALP) activity, and mRNA expression of reparative dentin-related genes. Furthermore, the dental pulp of the upper first molar in 8-week-old male ICR mice was exposed, and Thiamet-G was locally delivered for in vivo studies. Histological and immunohistochemical alterations were analyzed after 3 and 5 days post-cavity preparation, and dentin-bridge formation was evaluated at 42 days using histology and micro-CT.ResultsIn vitro, Thiamet-G treatment facilitated proliferation, ALP activity, and upregulated expression of reparative dentin-related genes, including BMP2, BSP, DSPP, OCN, and RUNX2. In vivo, Thiamet-G treated specimens showed the altered localizations of NESTIN, NF-κB, MPO, OPN, RUNX2, TGF-β1, and TNF-α at 3 and 5 days post exposure, suggesting enhanced dentin regeneration and modulated inflammation. Particularly, at 42 days, Thiamet-G treated specimens exhibited enhanced dentin-bridge formation, confirmed by micro-CT imaging and histology.ConclusionThiamet-G treatment facilitated reparative dentin formation by modulating inflammation and regulating regenerating signaling, suggesting its potential as a therapeutic agent.